3D modeliranje: Napredne tehnike in aplikacije v računalniško podprtem modeliranju - Ulbin, Miran (University of Maribor Press, 2024)
3D Modelling: Advanced Techniques and Applications in Computer-Aided Design (CAD). The textbook in the field of 3D modeling is intended as a study aid for the implementation of lectures on the subjects of 3D modeling and Computer Aided Design. It contains an explanation of most of the learning material that students need to master in these subjects, and is consistent with the curriculum of these subjects.